Genome-Wide Analysis Reveals Selection Signatures Involved in Meat Traits and Local Adaptation in Semi-Feral Maremmana Cattle - Ben-Jemaa, Slim; Senczuk, Gabriele; Ciani, Elena; Ciampolini, Roberta; Catillo, Gennaro; Boussaha, Mekki; Pilla, Fabio; Portolano, Baldassare; Mastrangelo, Salvatore (Frontiers in Genetics, 2021)
The Maremmana cattle is an ancient Podolian-derived Italian breed raised in semi-wild conditions with distinctive morphological and adaptive traits. Here, we aimed to detect potential selection signatures in Maremmana using medium-density single nucleotide polymorphism array. Putative selection signatures were investigated combining three statistical approaches designed to quantify the excess of haplotype homozygosity either within (iHS) or among pairs of populations (Rsb and XP-EHH), and contrasting the Maremmana with a single reference population composed of a pool of seven Podolian-derived Italian breeds. Overall, the three haplotype-based analyses revealed selection signatures distributed over 19 genomic regions. Of these, six relevant candidate regions were identified by at least two approaches. We found genomic signatures of selective sweeps spanning genes related to mitochondrial function, muscle development, growth and meat traits (SCIN, THSD7A, ETV1, UCHL1 and MYOD1) which reflects the different breeding schemes between Maremmana and the other Podolian-derived Italian breeds. We also identified several genes linked to Maremmana adaptation to the environment of the western-central part of Italy, known to be hyperendemic for malaria and other tick-borne diseases. These include several chemokine (C-C motif) ligand genes crucially involved in both innate and adaptive immune responses to intracellular parasite infections and other genes playing key roles in pulmonary disease (HEATR9, MMP28, ASIC2) or strongly associated with malaria resistance/susceptibility (AP2B1). Our results provide a glimpse into diverse selection signatures in Maremmana cattle and can be used to enhance our understanding of the genomic basis of environmental adaptation in cattle.